Rencana Pengembangan Sekolah Berbasis MBS - Harleli; Insan Islamanto; Nurrahman; Nur Afif (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
The school development plan based on SBM (School Based Management) is a strategic plan that focuses on strengthening schools as centers for effective decision making to improve the quality of education. The SBM concept emphasizes the importance of active involvement of all school stakeholders, including teachers, administrative staff, students, parents and the community, in the decision-making process and implementation of development programs. In contrast to the concept of External Control Management which makes parties outside the school, namely the government, the absolute and sole determinant of policy so that the school does not have broad authority. As a form of autonomy, school development plans can be implemented based on existing data and needs so that schools can develop positively. School development plans can be analyzed through surveys conducted on internal parties, namely teachers, education staff, students and parents, as well as input from external parties, namely the community and government.